The interaction effects of light and noise on the acoustic parameters of underwater vocalisations of wild spotted seals (Phoca largha) in Liaodong Bay, China1 - Yang, Liangliang (Frontiers in Marine Science, 2024)
Some marine mammals can adjust acoustic parameters of their sound signals in response to changes in sunlight and ambient noise. Evidence was found in several toothed whales; however, relatively little research has focused on true seals. Spotted seals (Phoca largha) are highly vociferous during the breeding season. Four major underwater call types, drums, growls, knocks, and sweeps, have been identified in the acoustic repertoire of wild spotted seals in Liaodong Bay, China. This study investigated the potential effects of light (day and night) and noise (105–135 dB re 1 μPa, broadband 50–8,000 Hz) conditions on the centroid frequency (CF), root-mean-square bandwidth (BW), duration (DU), and received level (RL) parameters of their underwater vocalisations using a series of generalised linear models (GLMs). Results showed that there were significant interaction effects of light and noise on knock CFs and the BWs for all call types. Specifically, knock CFs decreased and BWs for all call types became narrower when noise increased at night but kept stable during daytime. No significant interactions were found in other acoustic parameters. However, the results of univariate GLM analyses showed that the spotted seals could lengthen their vocalisations at night and increase the vocalisation RLs in response to higher noise levels (the Lambard effect), regardless of call type. To our knowledge, this is the first study to demonstrate that the spotted seals, a poorly studied species in Chinese waters, have some capabilities to adjust their vocalisations in response to changes in light and noise conditions. The results are helpful to understand how seals interact with their habitats and useful when developing mitigation strategies to minimise disturbance of light and noise from human activities in Liaodong Bay, China.